Relationship Between Water Birds’ Number and the Temperature in Beijing Wetland: A Case Study on Cuihu Wetland - Yu Rujin (E3S Web of Conferences, 2021)
Beijing is an important transfer station of bird migration, and its function as a bird habitat is very significant. Wetland birds have an extremely high reference value as ecological indicators and are greatly affected by climate change. This study takes waterbirds in Beijing Cuihu Wetland Park as the research object, carries out a statistical analysis of the number of birds in each year, and summarizes the relationship between them and Beijing's climate change. The results showed that Anatidae and Ardeidae accounted for a substantial part of wetland waterfowl, and their number was increasing year by year. There was a significant correlation between the monthly average number of two kinds of waterfowls and the average monthly temperature, and the negative correlation was found between the number of Anatidae and the average monthly temperature. The number of Anatidae and Ardeidae in spring and autumn are related to the monthly average temperature, seasonal average temperature and annual average temperature of the previous year.